Sex-linked amelogenin and Y-linked DBY gene sequence variations in Bos gaurus - Mok, Pei Chyi (2015)
The gaur, Bos gaurus, is classified as a vulnerable species as the population size is declining globally due to habitat loss, poaching and diseases from domestic cattle. Genetic studies on gaurs in Malaysia are limited; there is none on differentiating the two sexes using molecular markers. Molecular sexing is useful in identifying the gender of an animal, especially from the carcass parts, the meat, tissue and body fluid. This study was conducted to differentiate the male and female B. gaurus by the sequence variations of the sex-linked amelogenin gene and the Y-chromosome DEAD Box RNA Helicase 3 (DBY) gene. DNA from fecal samples of three male and three female gaurs were amplified using polymerase chain reaction (PCR) for these genes. A region of the amelogenin and DBY genes and amplicon sizes were estimated using electrophoresis as well as sequenced. Sequences were compared among themselves and with those of the B. indicus Kedah Kelantan (KK) which was used as a reference species. The fragment sizes and sequences for DBY did not show any variation between the males and females of both gaur and Kedah Kelantan; a sample DNA fragment of 180 bp was exhibited. DBY cannot be used to differentiate the two sexes for both gaur and B. indicus cattle. The amelogenin gene showed a single band pattern for the female KK (280 bp) and three bands (217, 280, and 340 bp) for the male KK but did give consistent results for the gaur samples.